Development of acid-free chitosan films in food coating applications: Provolone cheese as a case study - Casalini, Roberto; Ghisoni, Filippo; Bonetti, Lorenzo; Fiorati, Andrea; De Nardo, Luigi (Carbohydrate Polymers, 2024)
Chitosan has been extensively explored in food coatings. Still, its practical application is largely hampered by its conventional wet processing in acetic acid, whose residuals negatively impact food quality and safety. Here, we propose a new method to formulate chitosan coatings for food applications by avoiding organic acid processing and validate them on a cheese model. The procedure entails modifying a previously reported process based on HCl chitosan treatment and neutralising the resulting gel. The obtained chitosan is solubilised in water using carbonic acid that forms in situ by dissolving carbon dioxide gas. The reversibility of water carbonation allows for easy removal of carbonic acid residues, resulting in acid-free chitosan films and coatings. The performance of the coating was tested against state-of-the-art chitosan-based and polymeric coatings. We preliminarily characterised the films' properties (water stability, barrier, and optical properties). Then, we assessed the performance of the coating on Provolone cheese as a food model (mass transfer and texture profiles over 14 days). The work demonstrated the advantage of the proposed approach in solving some main issues of food quality and safety, paving the way for an effective application of chitosan in future food contact applications.